Explaining Trade in Ancient Western Asia - Yoffее, Norman
ersch. 1982; ad J. D. Hawkins (Ed.), Trade in the Ancient Near East (1977) and J. A. Sabloff - С. C. Lamberg- Karlovsky (Eds.), Ancient Civilizations and Trade (1975).